PENGARUH PH SALIVA TERHADAP KEKUATAN TARIK DIAMETRAL RESIN KOMPOSIT NANOHYBRID - Nilasary Rochmanita Suparno; Aulia Syahnas Nabila (Universitas Baiturrahmah, 2023)
Introduction: Nanohybrid composite resin is a restorative material that is often used because of its aesthetics and adequate mechanical properties. One of the mechanical properties of nanohybrid composite resins is diametral tensile strength, which affects the strength of composite resins when receiving chewing loads when used in the oral cavity. The value of the mechanical strength of the composite resin can be influenced by several factors, namely food, drink, and saliva. Human saliva has different pH levels and always interacts with restorative materials in the oral cavity. Objective: To determine the effect of salivary pH variations on the diametral tensile strength of nanohybrid composite resin. Methods: The materials used in the study were nanohybrid composite resin (Filtek Z250 XT, 3MESPE, USA), artificial saliva pH 4, pH 7, and pH 10. The type of research was a true experimental laboratory with a posttest-only control group design, which measured the diametral tensile strength of the nanohybrid composite resin that had been immersed in three treatment groups, namely the group immersed in saliva with pH 4, pH 7, and pH 10, with a total of 27 samples using the Universal Testing Machine (JTM, Taiwan). The results obtained were analyzed for one- way and post-hoc LSD variance. Results: Samples at acidic pH had the lowest average diametral tensile strength (39.09 MPa) compared to neutral pH (57.54 MPa) and alkaline pH (49.13 MPa). Statistical analysis showed significant differences between groups (p<0.05). Conclusion: Nanohybrid composite resin at neutral salivary pH has greater diametral tensile strength than at acidic or basic salivary pH